Delimiting the Origin of a B Chromosome by FISH Mapping, Chromosome Painting and DNA Sequence Analysis in Astyanax paranae (Teleostei, Characiformes) - Silva, Duilio M. Z. de A. [UNESP]; Pansonato-Alves, Jose Carlos [UNESP]; Utsunomia, Ricardo [UNESP]; Araya-Jaime, Cristian [UNESP]; Ruiz-Ruano, Francisco J.; Daniel, Sandro Natal [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Oliveira, Claudio [UNESP]; Camacho, Juan Pedro M.; Porto-Foresti, Fabio [UNESP]; Foresti, Fausto [UNESP] (Public Library Science, 2014)
Supernumerary (B) chromosomes have been shown to contain a wide variety of repetitive sequences. For this reason, fluorescent in situ hybridisation (FISH) is a useful tool for ascertaining the origin of these genomic elements, especially when combined with painting from microdissected B chromosomes. In order to investigate the origin of B chromosomes in the fish species Astyanax paranae, these two approaches were used along with PCR amplification of specific DNA sequences obtained from the B chromosomes and its comparison with those residing in the A chromosomes. Remarkably, chromosome painting with the one-arm metacentric B chromosome probe showed hybridization signals on entire B chromosome, while FISH mapping revealed the presence of H1 histone and 18S rDNA genes symmetrically placed in both arms of the B chromosome. These results support the hypothesis that the B chromosome of A. paranae is an isochromosome. Additionally, the chromosome pairs Nos. 2 or 23 are considered the possible B chromosome ancestors since both contain syntenic H1 and 18S rRNA sequences. The analysis of DNA sequence fragments of the histone and rRNA genes obtained from the microdissected B chromosomes showed high similarity with those obtained from 0B individuals, which supports the intraspecific origin of B chromosomes in A. paranae. Finally, the population hereby analysed showed a female-biased B chromosome presence suggesting that B chromosomes in this species could influence sex determinism.